KAJIAN PEMBEBASAN LAHAN OLEH PT. PERTAMINA GHEOTERMAL ENERGY TERHADAP NILAI LAHAN DI DESA TONSEWER SELATAN KECAMATAN TOMPASO BARAT - Steisi A. Mamesah; Mex Frans Lodwyk Sondakh; Yolanda Pinky Ivanna Rori (Sam Ratulangi University, 2020)
This study aims to determine the value of land that has been released whether it affects the value of land and determine the use of money from land acquisition in Tonsewer Selatan Village, Tompaso Barat Sub-district. This research was conducted in three months, from September to November 2019. The sampling method in this study uses a non-probability sampling technique or census sampling. The samples used in this study were 13 respondents, namely all farmers who own agricultural land who have sold their land so that land conversion has occurred. In this study using primary data obtained from direct interviews with respondents using a list of questions that have been prepared. Secondary data obtained from relevant agencies. The results showed that the value of the land acquired was higher in value than the present land value. This means that the value of land that has been acquired affects the current value of land. The money from the land acquisition has been used for various purposes, namely: for business capital, buying new land, saving, buying vehicles, renovating houses, and for daily needs.*eprm*